SUSTAINABLE INTERIOR DESIGN: STRATEGIES FOR CREATING ECO-FRIENDLY SPACES - Naaz, Shaila; Jain, Khushi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Recently, there has been a significant change in how interior environments are designed. The current design strategies emphasise creating healthy and sustainable spaces by using eco-friendly building materials and implementing suitable design solutions. This trend aims to promote environmentally responsible architecture and interior design (Alfuraty, 2020). When selecting materials and products for eco-friendly interior design, it is crucial to take into account various essential factors. These include low environmental footprint and impact, easy maintenance, high durability, adherence to budget constraints, comfort, safety, and flexibility (Jovanovic and Kekovic, 2019). The paper concludes that integrating sustainable design into interior architecture is essential for reducing environmental harm. Implementing measures to mitigate negative impacts is crucial (Ayalp, 2013). By using eco-friendly materials and following recommended selection criteria, designers can help create healthier and more sustainable interior spaces (Ayalp, 2013).